Is Food Supply Accessible, Affordable, and Stable? The State of Food Security in the Philippines - Ivory Myka R. Galang (Philippine Institute for Development Studies (PIDS), 2022)
Based on The Economist's 2021 Global Food Security Index (GFSI), the Philippines ranked 64th out of 113 countries in terms of its four dimensions of food security. After the World War II ended, the world still had to contend with population explosion, hunger, and poverty. The Philippines, just like other countries in the world, was actively searching for solutions through the conduct of research and the implementation of various agricultural programs and nutrition programs aimed at increasing food production and fighting the widespread malnutrition, especially among Filipino children. Since the term food security was officially defined and become popular in the late 1990s, it has been included in government laws, policies, and programs, such as the Agriculture and Fishery Modernization Act of 1997. This paper aims to evaluate the progress of AFMA implementation to date and assess prospects towards completing its Food Security objective. Using various indicators for the four dimensions of food security, namely, food availability, food accessibility, food utilization, and stability, the paper found that food security goal is yet to be achieved. Even the country's performance in achieving the Sustainable Development Goal (SDG) 2: Zero Hunger reflects that there have been some improvements, but significant and major challenges remain to be addressed. However, it is worth noting that the Department of Agriculture and other government agencies, which are tasked to develop the agriculture sector and ensure food security and nutrition, have made significant strides toward this goal, albeit falling short.
Keywords: 330; food security; food; AFMA; hunger; nutrition; food systems; food availability; self-sufficiency; food utilization; food accessibility; food affordability